THE IMPORTANCE OF TRANSLATION STUDIES IN THE PRESENT AND FUTURE - Sheraliyeva, Shaxnoza (Журнал иностранных языков и лингвистики, 2023)
Translation studies is a relatively new science in the world and not much is heard about it, let alone studied in Uzbekistan. Additionally, none of the universities in this country have a translation specialty or department. The translation is still seen as part of the language or literature faculty. Therefore, this article explains this new discipline, what it covers, and what trends it has in the present and future. This article aims to open the eyes of many academics in Indonesia who are learning about translation studies as a distinct science composed of many disciplines and to encourage people to learn more about this science.